A Fortified Complex at Pir Manakrai, Haripur: A Brief Introduction - Durrani, Mukhtar Ali; Jan, Zakirullah; Amin, Asim (Ancient Pakistan, 2021)
The archaeological site of Pir Manakrai is situated about 5 km east of Haripur city in the Hazara region of Khyber Pakhtunkhwa province, Pakistan between 33° 59 40” N and 72° 58 29” E (Fig. 1). It lies on the right bank of a hill stream called Dorr, which comes from the snowy peaks of the ‘gulliaf region of Abbotabad and debouches into the reservoir of Tarbela approximately 8 km to the north-west of the site. The mound is about 32 km north of the city of Takshasila (modern Taxila), and can be approached either from the village of Pir Manakrai, off-Chappar road from the north side, or by crossing the Dorr River at Ali Khan or Sarai Saleh villages on the Karakoram Highway to the south. The cultural deposit of the site lies scattered on three lower promontories named locally as Mathian, Sathian and Kathian, which cover an area of roughly 1.5 km. The meaning to these names is as obscured as the name of Pir Manakrai itself. Based on topography, the site can conveniently be divided into six units, which have been referred to as A, B, C, D, E and F (Fig. II) . . .